The Roman cemetery at Laurinova ulica in Vipava - Tratnik, Vesna; Miškec, Alenka (Arheološki vestnik, 2014)
The Roman cemetery at Laurinova ulica in Vipava yielded nine cremation graves in 2005. The graves span the 1st and 2nd centuries AD, as revealed by coins and other grave goods. The latter reflect a rather uniform picture that probably indicates typical burial rituals. The coins were laid into the graves after cremation, but only to adults; the burials of children did not reveal coin finds. The grave construction and goods indicate a strong influence and connections with the Italic world. There are, however, individual elements of a different, presumably local, indigenous burial tradition. An example of this is the burial of several individuals in the same grave; these are interpreted as family graves. The excavated part of the cemetery also allows certain conclusions to be drawn about the extent of the Roman settlement at Vipava.